UNVEILING ENGLISH LEARNING STYLE: A DESCRIPTIVE STUDY OF ENGLISH AS FOREIGN LANGUAGE (EFL) LEARNERS’ LEARNING STYLE - Etika Dewi Kusumaningtyas; Oktavia Nadia Salsabila (Journalistics: Journal of English Teaching and Applied Linguistics, 2025)
This research in title “Unveiling English Learning Style: a Descriptive Study of English as Foreign Language (EFL) Learners’ Learning Style”. Consideration of learning styles in education is crucial for improving the effectiveness of the learning process. Learning styles categorize into visual, auditory, visual- auditory and kinesthetic. By recognizing personal character of learning early, the learning process will be more effective and can be significantly improved. Adapting learning styles to the learning process can enhance comprehension, improve classroom interactions, and increase learning satisfaction. Recognizing g learning styles helps design teaching strategies but also impacts overall learning outcomes. this research awas conducted as descriptive qualitative research. This research intends to unveiling English as Foreign Language (EFL) learners’ learning style .